THE SIGNIFICANCE OF INTEGRATING LANGUAGE SKILLS IN THE PROCEDURE OF THE ENGLISH LANGUAGE TEACHING - Kristina, Kristina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article investigates the importance of language skills’ integration into the teaching process of the English language. The author of the research paper highlights integrating language skills concentrating on the four basic English skills - reading, writing, speaking and listening – with the aid of the “Communicative Language Teaching” methodology. Integrating language skills is concerned with authentic communication, insolate language students' realistic language and difficulties for them to interact naturally in the language. This technique promotes teachers to develop learners' achievements in multiple skills at a similar time. The research of authentic content is motivated by integrating language skills not just the dissection of language forms.